Aklimatyzacja poezji : Polsko-amerykańska antologia wierszy Anny Frajlich Between Dawn and the Wind .......... 287 - Luboń, Arkadiusz (Tu jestem / zamieszkuję własne życie : studia i szkice o twórczości Anny Frajlich, 2018)
ACCLIMATIZATION OF POETRY: THE POLISH-AMERICAN ANTHOLOGY OF ANNA FRAJLICH’S “POEMS BETWEEN DAWN AND THE WIND”The article discusses a set of translational techniques used by Regina Grol in her translations of selected poems by Anna Frajlich, collected and first published in the bilingual anthology “Between Dawn and the Wind”. As shown by the comparative analysis, numerous lexical choices and modifications were introduced during the transfer from source language (Polish) into target language (English) in order to match the meaning and form of the texts with the description of the poet provided by the translator. As a result, such features of Frajlich’s poetry as autobiographical references, focus on topics related to émigré identity or lyrical form based on simple and comprehensible language, are further enhanced by the textual alternations introduced by Grol.